ANALISIS PENCATATAN AKUNTANSI BERDASARKAN SAK-EMKM PADA USAHA BENGKEL DI KABUPATEN KARAWANG - Nur Wahyuni; Fista A. Sujaya; Meliana Puspitasari (AKUNTANSI DEWANTARA, 2023)
This study aims to determine the application of SAK-EMKM to UMKM in the car repair sector in East Karawang District. The method used in this study is descriptive qualitative through observation and interviews. Research analysis using data triangulation method. A car repair shop is one of the businesses that is easy to find in the East Karawang area. Financial reports based on SAK-EMKM include income statements, statements of financial position and notes to financial statements. The application of SAK-EMKM in car repair shops in East Karawang District has not gone well. Capital is one of the obstacles in applying SAK-EMKM accounting. Financial reports should have been implemented considering the importance of financial reports to assess financial performance.